Avaliação da qualidade e disponibilidade hídrica para abastecimento doméstico na cidade de Ituiutaba/MG - Penna, Maria Cristina Moreira (2020)
This study aimed to evaluate the quality and availability of water for supplying the city of Ituiutaba – MG. The importance of water conservation as a natural resource in the face of water problems faced in cities today and the need to maintain the quality and availability of water for human consumption, motivated this research. To achieve the general objective, methodological procedures were used divided into steps such as, bibliographic survey about the topics to be researched; characterization of the study area, including its social and economic aspects beyond the physical aspects; elaboration of a water balance to assess water availability; analysis of acquired data regarding water quality and final analysis of the data. the area of study for physical characterization was defined from a spatial clipping where they are the two water collection stations of the Water and Sewage Superintendence (SAE) are located in the municipality of Ituiutaba - MG, the main being in Ribeirão São Lourenço and the secondary in the middle course of the Tijuco River in the Salto de Moraes Plant Lake, in an extension of approximately 5 kilometers from the Tijuco River bank to the São Lawrence. To characterize the economic and social aspects, data referring to to the municipality. The final analysis of the data assesses the quality and availability of water as satisfactory to meet the domestic supply to the city of Ituiutaba - MG, but with caveat. The high water consumption in critical periods of water recharge in the basins hydrographic systems warns of the need for rational use so that demand does not make the insufficient availability in the future. As for water quality, SAE has shown efficiency in the services provided and, in order to maintain these results, it also depends on the collaboration of the population and public policies in relation to the use and occupation of the area of study, so that there is no contamination of water courses at such high levels that it is not possible to remove impurities from the water.